Disaster Regime Character: A Study of Disaster Risk Reduction at Merapi Volcano Eruption in Sleman Disrtrict - PARAMITA, NURLIA (Jurnal Studi Pemerintahan, 2012)
This research analyses how the existence of the character occurred in one of disaster managementphases which is an emergency response. In addition, it aims to discuss and see the relationshipbetween authority institutions in the disaster management which are Kesbanglinmas & PB Kab.Sleman, Muhammadiyah Disaster Management Centre (MDMC), and Merapi Circle InformationNetwork (JALIN MERAPI). This research uses qualitative method. The data about the policy andsurvivor handling are got through interviews with representatives from Pakem, Turi, andCangkringan. They are head of sub districts, head of villages, and head of country-sides. The findingsof this research show that the disaster regime character is fatalist-individualist and the authorityrelation is substitution (acts as a substitute). Therefore, humanity-based point of view is important tosee the risk. It will empower the capacity of government institutions. The last, involving civil society(CSO) is also significant to streamline the role of disaster management regime guide. Therefore, thesynergy between government and CSO will easily be achieved to implement Community-BasedDisaster Risk Management (CBDRM). CSO is the government’s partner to reduce disaster.